2020
DOI: 10.1038/s41594-020-0512-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ALT-associated homology-directed repair by polyADP-ribosylation

Abstract: The synthesis of poly(ADP-ribose) (PAR) reconfigures the local chromatin environment and recruits DNA-repair complexes to damaged chromatin. PAR degradation by poly(ADP-ribose) glycohydrolase (PARG) is essential for progression and completion of DNA repair. Here, we show that inhibition of PARG disrupts homology-directed repair (HDR) mechanisms that underpin alternative lengthening of telomeres (ALT). Proteomic analyses uncover a new role for poly(ADPribosyl)ation (PARylation) in regulating the chromatin-assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 54 publications
(82 reference statements)
1
20
1
Order By: Relevance
“…Furthermore, PARG activity was recently demonstrated to play a critical role in telomere extension through the alternative lengthening of telomeres (ALT) mechanism in cancer cells, including U2OS ( Hoang et al., 2020 ). Therefore, we decided to explore whether the additional loss of ARH3 would further impair this mechanism that is crucial for the survival of these cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, PARG activity was recently demonstrated to play a critical role in telomere extension through the alternative lengthening of telomeres (ALT) mechanism in cancer cells, including U2OS ( Hoang et al., 2020 ). Therefore, we decided to explore whether the additional loss of ARH3 would further impair this mechanism that is crucial for the survival of these cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…H3.3 G34R/V has, however, only been shown to obstruct SETD2 activity in cis 66,67 and this conjecture is therefore dependent on the mutant histone being incorporated into telomeric chromatin. In support of this possibility, recent work has shown that in the absence ATRX/DAXX, the histone H3.3 chaperone HIRA is enriched at ALT telomeres as an adaptive response to allow the deposition of histone H3.3 at telomeres 68 . A second mutation in histone H3.3 at lysine 27 to methionine (K27M) is also highly coincident with ATRX loss and inhibits the catalytic activity of PRC2 16,45,67 .…”
Section: Discussionmentioning
confidence: 95%
“…Whether nuclear F-actin promotes clustering of ALT telomeres, or their relocation to PML-NBs, is unknown. However, APB formation in ALT cells was suppressed when APR2/3 activity was inhibited, indicative of a link between nuclear cytoskeletal forces and ALT-activity [96].…”
Section: Hdr In Pml-nbsmentioning
confidence: 98%